HUMAN RESOURCE MANAGEMENT OF ISLAMIC EDUCATION IN THE DIGITAL ERA THROUGH THE INTEGRATION OF DIGITAL LITERACY AND QURANI ETHICS: A LITERATURE REVIEW - Mainur Andriya; Pablo Sindo; Syahril Yusuf; Afriza (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The digital era fundamentally changed Human Resource Management (HRM) in the field of education, demanding a new paradigm that integrates mastery of technology with spiritual and moral integrity. This study aims to analyze Islamic Education Human Resources Management in the Digital Era through the Integration of Digital Literacy and Quranic Ethics. This study uses the library research method, the results of the study show that effective educational resources in the digital era must shift from traditional administration to adaptive and ethical competency development. AI and Big Data demand not only technical skills, but also AI literacy to ensure critical, responsible, and ethical use, as well as reduce potential data bias. Furthermore, the integration of Islamic values such as trust, justice, and strong morals is central in creating a holistic learning environment. The recommended strategies include systematically increasing teacher capacity in digital leadership and a technology-integrated curriculum that remains firmly rooted in moral and spiritual principles derived from the Qur'an. This holistic approach is crucial to produce a competent and ethical generation, capable of competing globally while maintaining an Islamic identity.